Pang Ramung’s Resistance in Takengon (1901–1913): A Mixed-Methods Micro-History of Subaltern Agency in Colonial Aceh - Wiene Surya Putra; Karina Wanda (Saniya Institute, 2025)
This study investigates the anti-colonial resistance led by Pang Ramung in Takengon, Central Aceh, between 1901 and 1913, situating it within the broader context of the Aceh War. Using an explanatory sequential mixed-methods design, the research combines quantitative data from Dutch colonial records including demographic changes, infrastructure investment, and coffee production with qualitative analysis of archival documents and Gayo oral narratives (kekeberen). Drawing on social movement and postcolonial theory, the study analyzes how religious framing, leadership networks, and local terrain knowledge sustained resistance under colonial pressure. Findings reveal that Pang Ramung’s guerrilla tactics and the framing of the struggle as jihad fisabilillah fostered moral cohesion and strategic adaptation despite Dutch military superiority. Quantitative evidence shows that the 101-kilometer Bireuen–Takengon road and coffee plantation expansion paradoxically created vulnerabilities exploited by Gayo fighters. This research contributes to Indonesian historiography by foregrounding highland subaltern agency and demonstrating how ideology and infrastructure intersected in colonial resistance.